The conception of woman in Escola Doméstica de Natal’s curriculum (1914-1944) (Research, Society and Development, 2018)
This paper presents a discussion about the women's conception in the curriculum of Escola Doméstica de Natal, from 1914 to 1944. It aims to identify the planned training for the female population in this institution. The adopted methodology is based in an analytical study, by making comparisons between the collected information in the school's archive, as well as in the theoretical studies. At ED we had access to the institution's archive, in which it was possible to raise sources such as documents, reports and photos. The curriculum construction was based on these documents, on the data found in the newspaper A República and through the studies of Andrea Gabriel Francelino Rodrigues (2007). In addition, the theoretical studies allowed to find speeches given by Henrique Castriciano, by the Liga de Ensino do RN (LERN) and also through the Marques Neto (2005) studies. Through the presented curriculum we realized that the concept of women education in this period was directed to home and family. The reflections allows to notice that the woman, in Escola Doméstica's conception, was conceived as the social change pillar, taking into account her position in the family. The LERN defended the same percepts in which women education should be the one where the woman would know how to guide herself in the ways of life at home or outside it. In the course of the research we realized who was that woman in the beginning of the 20th century and which were the contributions of the Escola Doméstica for the construction of this feminine ideology.